Theoretical contributions to the management of sports organizations. (Impetus, 2025)
The diversity of meanings and approaches to sport as a social phenomenon, coupled with globalization and technological advances, motivate various academics and researchers in Latin America to approach the topic from different disciplinary perspectives of human knowledge. A growing number of texts delve into topics related to sport. The field of sports management is no exception, given that sports organizations face challenges that require a multidisciplinary analysis of their organizational processes to contribute to efficient and effective performance, particularly the management process. In this context, the book "New Trends in Sports Management" appears on the academic and scientific scene as a collection of articles and essays, whose compilers (Darío Espinal Ruíz and Daniel Carranza Bautista) undertook the task of developing, analyzing, and selecting quality thematic works in this area, under a rigorous academic review process.
Keywords: Management; Administration; Research trends; Sports organizations